Panduan cara pemberian skor dan analisis untuk menilai kesejahteraan manusia - Salim, A.; Colfer, C.J.P.; McDougall, C. (Center for International Forestry Research, 2000)
This is designed to supplement 'the BAG' and 'the Grab Bag'. It provides a scoring method that can be used with the two manuals, to come to a decision about particular criteria and indicators in particular forest and human settings. Following the section on scoring is a section on analysis. It begins very simply, leading the user through the steps of making a spreadsheet, and concluding with more complex statistical analyses that may be desirable in some circumstances. Different teams have different requirements for quantitative and statistical sophistication in their analyses. This manual responds to these differing needs.